Business Analysis to Strengthen Wifi ID Investment Project at PT. Telekomunikasi Indonesia Tbk. - Luthfi Rusminar, Ressa; Kaderi Wiryono, Sudarso (The Indonesian Journal of Business Administration, 2016)
Abstract –In 2012, Telkom start the strategy initiation achieve widespread broadband penetration throughout Indonesia through the implementation of the Indonesia WIFI program towards the development of IDN. Wifi.id is a white label WiFi broadband access network to deliver high speed internet access as well as various other multimedia services. Telkom built wifi business with standalone business model. In 2015 Telkom has plan to roll out its business plan for 7 years from 2016 untill 2022 because gap between deployment and achievement. Relocation of access point and partnership business strategy will be an opportunity for Telkom to monetise Wifi ID investment project. The planning is expected could affect Telkom’s long-run equity performance. The connections between capital structure and investment decisions should be most apparent when a company undertakes a large investment. This paper proposes to conduct the development of alternative strategies in context to determine and allocate the optimized investment decision which is result to create and maximize firm’s value through investments in Wifi ID investment projects. Using the method of investment decision based on the criteria of cash flow, bottom-up method to determine the industry beta, the result of analysis show that with three scenario planning (conservative, base and stretch), Wifi Investment Project ID as feasible by the two scenarios, that is base and stretch. Then based on the theory of decision-making, investments that achieve the optimal gain is investment in the consumer sector (CONS) and wholesale (WINS). Keyword: Investment decision, cash flow based method, capital structure